Sekilas tentang Risiko dan Penyelesaian Hukum terhadap Kredit Macet - noor hafidah (Fakultas Hukum Universitas Islam Indonesia, 2002)
The Resolution of many unpaid debts needs a legal comprehensif approach. It means that although the basic needislegal aspect, however, its hould bebasedonthelegal rule. How the ideal of legal accessories can playln' the resolution of unpaid debts, such consistenly implements the rule as in the banking law, not bythe other rule norbyillegalways. The Illegal ways can bring to the unjustice oflaw